The expression of endothelin-1 in chronic lymphocytic leukemia is controlled by epigenetic mechanisms and extracellular stimuli. (March 2017) - Martinelli, Silvia; Maffei, Rossana; Fiorcari, Stefania; Quadrelli, Chiara; Zucchini, Patrizia; Benatti, Stefania; Potenza, Leonardo; Luppi, Mario; Marasca, Roberto
Highlights: ET-1 basal level in CLL is affected by methylation of the first gene intron. CD40 activation increases the levels of ET-1 in CLL. In CLL, TLR stimulation induces higher ET-1 expression. NF-kB signalling pathway is important in promoting and maintaining ET-1 expression in CLL. Abstract: Endothelin-1 (ET-1) is a hormone peptide widely expressed and is involved in several biological processes, important not only for normal cell function but also for tumor development, including cell proliferation, invasion, metastasis, angiogenesis and osteogenesis. In accordance, ET-1 was already shown to contribute to the growth and progression of many different solid cancers. We recently demonstrated that ET-1 has a role in the pathogenesis of chronic lymphocytic leukemia (CLL) where it is abnormally expressed. In the context of this malignancy, ET-1 is able to mediate survival, drug-resistance and growth signals in leukemic cells. Previous studies, not conducted in CLL, have shown that ET-1 regulatory mechanisms are numerous and cell specific. Here, we valued the expression of ET-1 in CLL, in relation to DNA methylation but also in response to stimulation of some important pathways for the dialogue between CLL and microenvironment. We found that a high methylation of ET-1 first intron affects the basal expression of ET-1 in CLL. Moreover, we showed that the activation of CD40 or Toll-like receptor (TLR) by extracellular stimuli produces an augment of ET-1 level in CLL cells. Finally, we demonstrated the fundamental role of NF-kB signalling pathway in promoting and maintaining ET-1 expression in CLL cells, both in basal conditions and after CD40 activation.